Effect of Prilled Urea, Urea and NPK Briquettes on the Yield of Bitter Gourd in Two Upazillas of Jessore District (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted to evaluate the performance of deep placement of urea and NPK briquettes compared to broadcast application of prilled urea for bitter gourd production during the Kharif-1 season of 2013. The experiments were conducted in two locations in Jessore district, Chowgacha and Jessore sadar. Seven treatments were designed to evaluate crops response: T1: Control, T2: Farmers practice, T3: Recommended doses of all fertilizers except N, T4: Recommended doses of all fertilizers, T5: Urea briquette + other fertilizers, T6: NPK briquette + other fertilizers and T7: NPK briquette + other fertilizers except cowdung. The rate of urea and NPK briquette was 10 percent less than the rate of recommended prilled urea. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The sizes of NPK and urea briquette were 3.4 g and 2.7 g, respectively. The recommended fertilizer doses were used to supply N, P, K, S, Zn and B from Urea, TSP, MoP, gypsum, zinc sulphate (hepta) and boric acid, respectively. The results showed that deep placement of NPK briquette gave significantly the highest yield of bitter gourd (32.16 tha-1) followed by urea briquette (30.45 tha-1) which were 12.34 and 7.41 percent higher over recommended doses of all fertilizers. The highest N recovery (77.4 %) was found when 72 kg N ha-1 was applied as NPK briquette.J. Environ. Sci. & Natural Resources, 8(1): 157-160 2015